2011
DOI: 10.1007/s00438-011-0636-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of gene-based simple sequence repeats across Brassica species

Abstract: Simple sequence repeats (SSRs) are important components of eukaryotic genomes and may play an important role in regulating gene expression. However, the characteristics of genic SSRs and the effect of interspecific hybridization and polyploidization on genic SSRs seem not to have received desired attention in terms of scientific investigations. To determine the features of genic SSRs and elucidate their role in polyploidization process of the Brassica family, we identified SSRs in Plant Genome Database-assembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
2
16
0
1
Order By: Relevance
“…This was consistent with previous findings: the frequencies of microsatellites in the transcribed sequences/unigenes of A. thaliana , B. rapa and B. oleracea were lower than that of B. napus [14], [26]; the duplicated genes in Arabidopsis typically contained a higher frequency of microsatellites [10]. These results strongly suggested that polyploidy may lead to the slight increase in the frequency of microsatellites in the coding sequences, which may be advantageous for evolution because microsatellites in coding sequences can be directly linked to gene function, providing a basis for quick adaptations to environmental changes [1], [4], [27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This was consistent with previous findings: the frequencies of microsatellites in the transcribed sequences/unigenes of A. thaliana , B. rapa and B. oleracea were lower than that of B. napus [14], [26]; the duplicated genes in Arabidopsis typically contained a higher frequency of microsatellites [10]. These results strongly suggested that polyploidy may lead to the slight increase in the frequency of microsatellites in the coding sequences, which may be advantageous for evolution because microsatellites in coding sequences can be directly linked to gene function, providing a basis for quick adaptations to environmental changes [1], [4], [27].…”
Section: Discussionsupporting
confidence: 93%
“…The current investigation also revealed several constant microsatellite characteristics in plant evolution, as the observed high level of consistency among all the species investigated in this and other studies [8], [9], [14], [15], [25], [45], [57], [58], [59] was not likely a chance event. First, trinucleotide repeat microsatellites were dominant in coding sequences (Figure 3; Table 3), which is undoubtedly caused by the triplet nature of codons [4].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A potential explanation for the high ratio of mononucleotide SSR loci in this study was that mononucleotide SSRs would be amplified rapidly after interspecific hybridization (Gao et al 2011). The repeat units of 10, 5, 11, and 6 about SSR sequences account 69.73 % of the total SSRs, thus a rough trend could be discerned where the size of SSRs mainly ranged from 10 to 18 bp (Table 2).…”
Section: Discussionmentioning
confidence: 85%
“…Markers obtained from the gene space of a species, are most informative. EST-cDNA probes [14,41], genic SSRs [42,43], intron polymorphism (IP) markers [15,43] and InDels (Sequence Tagged Sites, STS) [44], have all been successfully used for comparative mapping and studying genomic synteny amongst the Brassica species belonging to the U’s triangle [9]. …”
Section: Discussionmentioning
confidence: 99%